Ecdysone triggered PGRP‐LC expression controls Drosophila innate immunity. (7th May 2013) - Rus, Florentina; Flatt, Thomas; Tong, Mei; Aggarwal, Kamna; Okuda, Kendi; Kleino, Anni; Yates, Elisabeth; Tatar, Marc; Silverman, Neal
<x xml:space="preserve">Abstract</x> Throughout the animal kingdom, steroid hormones have been implicated in the defense against microbial infection, but how these systemic signals control immunity is unclear. Here, we show that the steroid hormone ecdysone controls the expression of the pattern recognition receptor PGRP‐LC in Drosophila, thereby tightly regulating innate immune recognition and defense against bacterial infection. We identify a group of steroid‐regulated transcription factors as well as two GATA transcription factors that act as repressors and activators of the immune response and are required for the proper hormonal control of PGRP‐LC expression. Together, our results demonstrate that Drosophila use complex mechanisms to modulate innate immune responses, and identify a transcriptional hierarchy that integrates steroid signalling and immunity in animals.